Population structure and habitat preference of cave crickets (Rhaphidophora sp. (Orthoptera: Rhaphidophoridae)) in Sanghyang Kenit cave, Citatah karst area, West Java - Isma Dwi Kurniawan; Rahmat Taufiq Mustahiq Akbar; Risda Arba Ulfa; Mentari Kusuma Wardani; Birama Satria (Journal of Tropical Biodiversity and Biotechnology, 2022)
Cave crickets are considered as a keystone species that can be used as a cave ecosystem bioindicator. Developing caves as tourism has considerable potential to disturb cave cricket populations. This study aimed to investigate cave cricket population structure and their habitat preference in Sanghyang Kenit cave one year after it developed into a show cave. Data were collected through standardized visual searching in three cave zones: entrance, twilight, and dark. Besides cave crickets, other macroarthropods discovered in each zone were also recorded. Abiotic parameters of habitat comprised air and soil temperatures, RH, soil moisture, soil pH, and light intensity were measured. Data were analyzed to show cave crickets abundance, density, sex ratio, and age structure. Statistical analysis comprising Kruskal Wallis, non-metric multidimensional scaling, and correlation tests were performed. The cave cricket population in Sanghyang Kenit belonged to a single species, Rhaphidophora sp. The population was around 78-108 individuals and distributed in all cave zones. The abundance and density in twilight and dark zones were significantly higher than in the entrance. The number of males outperformed females with a 2.16 ratio. Besides, the population was dominated by the sub-adult class. Environmental parameters of twilight and dark zones tended to be similar to one another compared to the entrance. Cave crickets preferred habitats with dark, humid, and acidic soil pH. Heteropoda sp. and Catagaeus sp. were considered potential predators. This study implies the importance of protecting cave crickets in Sanghyang Kenit.